Ricardo Muñoz Martín (ed.) 2014. Minding Translation. Con la Traducción en Mente. MonTI. Special issue 1. Universitat d'Alacant, Universitat Jaume I, Universitat de Valencia. ISSN: 1889-4178 - Schrijver, Iris (HERMES - Journal of Language and Communication in Business, 2016)
No abstract